Work hardening behavior of nanotwinned austenitic grains in a metastable austenitic stainless steel. (15th March 2016) - Yi, H.Y.; Yan, F.K.; Tao, N.R.; Lu, K.
Abstract: The work hardening behavior of nanotwinned austenitic grains in a novel type of nanotwinned austenitic stainless steels was investigated. Multiple Shockley partial dislocation activities in the nanotwinned grains could trigger occurrence of stacking faults and strain induced martensitic transformation before necking, resulting in an increase in work hardening rate. Consequently, the fully recovered nanotwinned austenitic stainless steel exhibits a uniform elongation of ~ 13% at the strength of 950 MPa. Graphical abstract: